Surveillance of canine visceral leishmaniasis in a disease-free area - Frehse, Michele Salmon; Greca Júnior, Haroldo [UNESP]; Ullmann, Leila Sabrina [UNESP]; Camossi, Lucilene Granuzzio [UNESP]; Machado, Juliana G. [UNESP]; Langoni, Hélio [UNESP]; Biondo, Alexander Welker; Molento, Marcelo Beltrão (My University, 2010)
Leishmaniasis is an important re-emergent parasitosis worldwide, particularly in tropical countries. There are no reports of autochthonous disease in the State of Paraná, southern Brazil. No surveillance has been carried out in the most populated areas such as the city of Curitiba and its surroundings. The purpose of the present study was to determine the seroprevalence of visceral leishmaniasis in dogs at the Center for Zoonosis Control of São José dos Pinhais, Paraná, before euthanasia. Enzyme-linked immunosorbent assay (ELISA) and immunofluorescence antibody test (IFAT) were used to detect antibody levels against Leishmania sp. in dog sera. Imprints of the popliteal lymph nodes that were also randomly collected from 50 dogs with suspected clinical signs of visceral leishmaniasis, and evaluated under light microscopy for the detection of amastigote forms, were negative. A total of 364 dog samples were tested. The results showed only one positive sample (0.0027%) by ELISA test but negative by IFAT, however, the dog had no clinical signs. Random surveillance of dog populations from several districts of a metropolitan area may be a means of preventing Leishmania spreading. Based on our results, the city of Curitiba and its metropolitan area were considered at low risk for visceral leishmaniasis.
Vigilância da leishmaniose visceral canina em área indene
Keywords: Dog; ELISA; Leishmania sp.; RIFI; Zoonoses